More Deaths Than Births: Subnational Natural Decrease in Europe and the United States. Issue 4 (December 2015) - Johnson, Kenneth M.; Field, Layton M.; Poston, Dudley L.
Abstract : This article examines the prevalence and dynamics of natural decrease in the subnational populations of Europe and the United States. Natural decrease results from interactions between fertility, mortality, and migration over a protracted period. We document the greater incidence and degree of natural decrease in Europe. In the first decade of the twenty‐first century, natural decrease occurred in 58 percent of European NUTS 3 areas ("counties") compared to only 28 percent of the US counties. Three critical demographic variables (proportion over 65, child‐women ratio, and proportion of women of childbearing age) each exert a significant and distinct impact on the likelihood of natural decrease. Our spatial regression models reflect remarkable consistency in the influence of each of these variables in Europe and in the US, demonstrating the similarity in the demographic processes that produce natural decrease.